Effectiveness of the blended-care lifestyle intervention 'PerfectFit': a cluster randomised trial in employees at risk for cardiovascular diseases - Tessa A. Kouwenhoven-Pasmooij; Suzan J. W. Robroek; Roderik A. Kraaijenhagen; Pieter H. Helmhout; Daan Nieboer; Alex Burdorf; M. G. Myriam Hunink (BMC, 2018)
Abstract Background Web-based lifestyle interventions at the workplace have the potential to promote health and work productivity. However, the sustainability of effects is often small, which could be enhanced by adding face-to-face contacts, so-called 'blended care'. Therefore, this study evaluates the effects of a blended workplace health promotion intervention on health and work outcomes among employees with increased cardiovascular risk. Methods In this multicentre cluster-randomised controlled trial (PerfectFit), 491 workers in 18 work units from military, police, and a hospital with increased cardiovascular risk were randomised into two intervention groups. The limited intervention (n = 213; 9 clusters) consisted of a web-based Health Risk Assessment with advice. In the extensive intervention (n = 271; 8 clusters), coaching sessions by occupational health physicians using motivational interviewing were added. One cluster dropped out after randomisation but before any inclusion of subjects. Primary outcome was self-rated health. Secondary outcomes were body weight, body mass index (BMI), work productivity, and health behaviours. Follow-up measurements were collected at 6 and 12 months. Effect sizes were determined in mixed effects models. Results At 12 months, the extensive intervention was not statistically different from the limited intervention for self-rated health (4.3%; 95%CI -5.3-12.8), BMI (− 0.81; 95%CI -1.87-0.26) and body weight (− 2.16; 95%CI -5.49-1.17). The within-group analysis showed that in the extensive intervention group body weight (− 3.1 kg; 95% CI -2.0 to − 4.3) was statistically significantly reduced, whereas body weight remained stable in the limited intervention group (+ 0.2 kg; 95% CI -1.4 to 1.8). In both randomised groups productivity loss and physical activity increased and excessive alcohol use decreased significantly at 12 months. Conclusions There were no effects on self-rated health, body weight, and BMI. However, within the group with web-based tailored Health Risk Assessment including personalized advice body weight reduced significantly. Adding motivational coaching is promising to reduce body weight. Trial registration Retrospectively registered at the Netherlands Trial Registry with number NTR4894, at Nov 14 2014.